Digital reference services using web services: Overview, design and specifications - Julaily Aida, Jusoh; Mohd Nordin, Abdul Rahman; Magaji Zainab, Musa (Asian Research Publishing Network, 2015)
Digital reference service (DRS) is an emerging trend of traditional reference service. Easily accessible digital reference service that provides real time service to the patrons has become one of the necessities of the library information systems. Implementing a networked synchronous digital reference service by most libraries has become a difficult task. Web services on the other hand allow interoperability between heterogeneous devices and applications provided that they have conformed to the web services protocols. This paper gives an overview of digital reference service and web services applications. It uses questionnaires to make a survey in some university libraries so as to find out the actual problems faced by patrons while using DRS and also to know the specific requirements of the patrons. It provides a means of eradicating the present problem of digital referencing in the libraries by proposing a model for using web services technology in developing networked synchronous digital reference services. The functional informal specifications of the proposed model are also provided.